Studi Efek Skala pada Uji Kuat Tekan Uniaksial Terhadap Batupasir Pada Formasi Balikpapan Daerah Samarinda Utara, Provinsi Kalimantan Timur - Milda Milda; Tommy Trides; Harjuni Hasan; Revia Oktaviani; Agus Winarno (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
Scale effect testing on rocks is carried out with the aim of knowing the strength of a rock based on different dimensions. This test was carried out using a uniaxial compressive strength test and also testing the physical properties of rocks. In the rock compressive strength test used 5 dimensions of rock samples with a H/W ratio of which are 4.5/3, 6/3, 7.5/3 for dimensions of 3 cm, 5.25/3.5, 7 /3.5, 8.75/3.5 for dimensions 3.5 cm, 6/4, 8/4, 10/4, for dimensions 4 cm, 6.75/4.5, 9/4.5, 11.25/4,5 cm for the 4.5 cm dimension and for the 5 cm dimension, namely 7.5/5, 10/5 and 12.5/5. Physical properties testing is carried out to determine the porosity value in the test rock samples, which will then be compared between the porosity values ​​and the results of the compressive strength test of rock samples. Physical properties testing carried out obtained the average value of rock porosity, namely 22.562%, 22.122%, 20.454%, 21.227%, and 22.413%. In the scale effect test, it is known that the higher the rock sample, the smaller the value of the rock strength can be seen based on the R2 value obtained in the Balikpapan Formation, which is 0.0548.